The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0074-02762003000400003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clostridium spp. and Clostridium difficile in children with acute diarrhea in São Paulo city, Brazil

Abstract: Species of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…82 The authors concluded that the isolation rate was not significant enough to account for the difference in symptoms between the two groups.…”
Section: Case Control Studiesmentioning
confidence: 98%
“…82 The authors concluded that the isolation rate was not significant enough to account for the difference in symptoms between the two groups.…”
Section: Case Control Studiesmentioning
confidence: 98%
“…The high prevalence of ribotype 017 led the authors to conclude that not only has this C. difficile type gradually replaced other circulating PCR-ribotypes in this hospital, but it could also be associated with a similar spectrum of clinical disease as that caused by tcdA + /tcdB + strains. Ferreira et al (2003) analysed 181 stool samples that were collected over 1 year from children (0-5 years of age) with acute diarrhoea who were admitted to three different hospitals. Samples were also collected from healthy children (without diarrhoea).…”
Section: Argentinamentioning
confidence: 99%
“…A small study in Brazil attempted to compare strains of C. difficile in hospitalised children with acute diarrhoea with asymptomatic children recruited from day-care centres, but none of the controls were culture positive for C. difficile. Nine out of the ten strains isolated from symptomatic patients were toxigenic: six were tcdA +/tcdB + and three were tcdA−/tcdB + [54].…”
Section: Explanations For High Levels Of Asymptomatic Colonisationmentioning
confidence: 99%